The contribution from cross-country skiing and shooting variables for biathlon performance in sprint, individual and pursuit competitions - Luchsinger, H. (Norwegian University of Science and Technology, 2021)
Biathlon is an Olympic winter sport combining cross-country (XC) skiing in the skating technique with rifle marksmanship. Biathletes ski loops of 1.5-4 km with shooting between laps in either the prone or standing position. The cross-country (XC) skiing part of the competition is performed on XC-skiing tracks on undulating terrain differing between uphill, downhill and flat or varied terrain. The shooting takes place directly between each lap of skiing on a 50 m outdoor shooting range where the circular targets have hit areas of 45 mm in prone position and 115 mm in standing. Biathletes use 0.22 caliber rifles that the athletes carry on their back while skiing. In single-start races each shooting comprises of 5-shot-series in the prone or standing shooting. For each missed target at the shooting range, biathletes are either penalized with extra time (i.e. 60 s in the individual 15/20 km event) or a 150 m extra loop of skiing (~22s). Seven championship biathlon events exist with varying skiing distances for each shooting and penalty for missed targets across events. The overall purpose of this thesis was to study the contribution of the different race components in biathlon sprint, individual and pursuit races in both genders as well as the association between sprint race performance and laboratory measured capacities.